Neutralization of enterotoxins of Escherichia coli by coleonol (Forskolin) in rabbit and guineapig ileal loop models - YADAVA, J N S; GUPTA, SHASHI; AHMAD, IQBAL; VERMA, NEERAJ; TANDON, J S (The Indian Journal of Animal Sciences, 2013)
A crude alcoholic extract of Coleus froskohlii Briq. roots showed marked inhibitory action against Eschrichia colt toxin induced secretary response at 300 mg/100 p dose in rabbits and guncapig ileal loops. Coleonol A and B obtained by column chromatography of a henzene fraction of the aicoholic extract of Coteus froskushlu roots exhibited antisecrery (antidiarrhocal)activity at 1 mg does/loop. Coleonol-A showed nearly 79% inhibition against heat labilc LT) toxin and 67% against heat stable (ST) toxin induced secretions However, coleonol-B exhited less activity against ST (68.3%) enteroloxins as compared to the widely used antidiarrhoeal (antisecrotory) drug. Loperamide (an opiate aganist) which showed 77 and 65% inhibution against LT and ST toxins, respectively, at a similar does.